2020
DOI: 10.1093/qjmed/hcaa159
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of doctors’ fatality due to COVID-19 in Western Europe and Asia-Pacific countries

Abstract: Under the coronavirus disease 2019 (COVID-19) pandemic, the deaths of healthcare professionals have been increasingly reported worldwide. We performed a cross-sectional, observational study using news reports on the websites among selected countries as of April 2020. We found 120 dead medical doctors due to COVID-19 in Western Europe and Asia-Pacific countries; 67 in Italy (47 in the Northern part), 34 in China (22 in Hubei), 6 in France, 4 in the UK, the USA and Spain and 1 in South Korea, respectively. Among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 4 publications
0
18
0
1
Order By: Relevance
“…As COVID-19 pandemic continues, the death of physicians has been increasingly reported worldwide. A recent cross-sectional study published in April 2020 showed that 120 medical doctors have died due to COVID-19; 67 in Italy, 34 in China, 6 in France, 4 in the United Kingdome (UK), the United States of America (USA), and Spain and 1 in South Korea [6].…”
Section: Introductionmentioning
confidence: 99%
“…As COVID-19 pandemic continues, the death of physicians has been increasingly reported worldwide. A recent cross-sectional study published in April 2020 showed that 120 medical doctors have died due to COVID-19; 67 in Italy, 34 in China, 6 in France, 4 in the United Kingdome (UK), the United States of America (USA), and Spain and 1 in South Korea [6].…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies, there is much anxiety, fear and bereavement amongst GP team members at the present time not only due to increased mortality rate caused by the virus, but also related to increased risk of severe complications, changes in professional practice concerns with loss of face-to-face human connection [ 16 ]. Moreover, under the COVID-19 pandemic, physicians caring for COVID-19-infected patients have been endangered by the risk of contagion and possible mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In view of this point, the sufficient supply of personal protective equipment and the education of how to use it [ 19 ] can greatly relieve their negative psychological changes. Also, the effective collaborative team working and understanding from friends and families can be helpful [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, risk assessment must be carried out among health professionals and supporting staff so that the interaction of high-risk staff with suspected COVID-19 cases is properly managed [185][186][187][188][189]. The disease has claimed the lives of many health workers at different levels despite the standards and quality of healthcare settings [190][191][192].…”
Section: Practicing Ramadan Fasting During the Covid-19 Pandemicmentioning
confidence: 99%